Attention-Deficit Hyperactivity Disorder Symptoms in A Group of Children Receiving Orthodontic Treatment in Turkey - (:unkn) unknown (AVES, 2020)
Objective: Children with attention-deficit hyperactivity disorder (ADHD) are known to have several oral health problems, particularly traumatic dental injuries, decayed or filled teeth, and poor oral hygiene. The objective of the present study was to determine the ADHD symptoms in a group of patients with malocclusion and receiving orthodontic treatment. Methods: A total of 88 subjects with a diagnosis of malocclusion between aged 8 and 17 years were included in the study. Socio-demographic characteristics, breastfeeding history, oral habits, and dental trauma history of the subjects were acquired by a detailed questionnaire. Subjects and their parents completed questionnaires addressing ADHD, other psychiatric problems, and dental health impact on the quality of life. During the orthodontic examination, the Index of Complexity, Outcome, and Need was applied to confirm the diagnosis of malocclusion. Results: Parent-reported psychiatric complaint occurred in almost half of the patients (n=38, 43.2%); the most frequent psychiatric complaints were inattention (n=22, 25%), opposition (n=13,14.8%), and hyperactivity (n=11, 12.5%).The estimated ADHD prevalence according to parent measure was 15.9% (n=14). Self-report measures revealed that 18.4% (n=16) had behavioral symptoms.The most affected quality of life domain was psychological discomfort. Conclusion: The findings indicate that ADHD prevalence in children with malocclusion is high. The orthodontists should have a keen eye on behavioral problems.
Keywords: Attention-deficit hyperactivity disorder; malocclusion; behavior; orthodontics; TRAUMATIC DENTAL INJURIES; ORAL-HEALTH STATUS; QUALITY-OF-LIFE; DEFICIT/HYPERACTIVITY DISORDER; PSYCHOMETRIC PROPERTIES; ADOLESCENTS; SCHOOL; ADHD; MALOCCLUSION; POPULATION